Harnessing immunological targets for COVID-19 immunotherapy - Mehata A.K.; Viswanadh M.K.; Priya V.; Vikas; Muthu M.S. (My University, 2025)
COVID-19 is an infectious and highly contagious disease caused by SARS-CoV-2. The immunotherapy strategy has a great potential to develop a permanent cure against COVID-19. Innate immune cells are in constant motion to scan molecular alteration to cells led by microbial infections throughout the body and helps in clearing invading viruses. Harnessing immunological targets for removing viral infection, generally based on the principle of enhancing the T-cell and protective immune responses. Currently-approved COVID-19 vaccines are mRNA encapsulated in liposomes that stimulate the host immune system to produce antibodies. Given the vital role of innate immunity, harnessing these immune responses opens up new hope for the generation of long-lasting and protective immunity against COVID-19. © 2021 Future Medicine Ltd.. All rights reserved.